Alienação parental: revisão conceitual e comparação do conhecimento de profissionais e estudantes de psicologia - Gama, Viviane Dutra (Universidade Federal de São Carlos, 2019)
There is no consensus on the literature regarding the definition of Parental Alienation (PA), fact that hinders the measurement, assessment and research of the phenomenon. Despite that, Brazil has a law that punishes the practice of alienation although this phenomenon is not well documented on academic circles yet. Considering the conceptual frame on PA and its specificity in the Brazilian context, the present study had two main goals, presented in two articles: 1) to propose an operational definition of the PA concept based an a ten-year systematic literature review, and 2) to investigate the knowledge of Psychology students on PA and to compare their answers in simulated alleged PA cases with the answers from psychologists. The search was conducted on 5 databases and 339 articles were found. Sixty-three papers were analyzed considering the definitions and use of PA and Parental Alienation Syndrome (PAS), authors’ attitudes towards PAS and recognition of PA as a modality of psychological abuse. Additionally, analysis and functional classification of parental alienation strategies mentioned on the articles was conducted. From the literature reviewed, Parental Alienation can be defined as a modality of psychological violence or abuse perpetrated against the child by a parent, caretaker, or family member, in which the behaviors emitted by the alienating member have the function of showing hostility and/or estranging the child from the alienated part. Ninety-one Psychology students participated on the research that involved collecting empirical data. Participants answered an online survey that assessed their familiarity with the PA concept, factors considered important and procedures they would use when conducting PA assessment. In addition, vignettes containing PA simulated cases were presented. The number of professionals who answered the vignettes varied between 42 to 58 and their answers were previously collected and registered on a database. In terms of students` knowledge, the results indicated that 72.5% of them reported to be familiar with the PA concept. Students were more accurate in evaluating the vignette involving a possible PA case, while professionals evaluated the case where PA allegations occurred simultaneously to sexual abuse allegations in a more accurate way. Given the reported results, one may conclude that the field of PA is characterized by strong conceptual divergences. As a consequence, the assessment of this phenomenon is a challenge both for forensic professionals and students.
Parental alienation: literature review and comparison of knowledge from psychology students and professionals
Keywords: Alienação parental; Revisão conceitual; Estudantes universitários; Casos simulados; Parental alienation; Conceptual review; College students; Simulated cases; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA